4 - Défis du passage au LMD dans les universités congolaises : cas de l’Université de Kinshasa - Pascal Kapagama Ikando (Journal of Higher Education in Africa, 2009)
The Congolese university, founded in 1964, had inherited the university system of its former colonial metropolis, Belgium. Its route was marked by several reforms. Recent reforms in 1981 and 2004 did not help the Congolese university education system to adapt gradually to universal transformations concerning university curricula which the Bologna reform has established with the introduction of the BMD in the European University system. In its strategic plan for its rehabilitation and revitalization by 2010, the University of Kinshasa has committed to consider and adopt a diploma structure based on the BMD model. Thus, considering both the different conceptions of the BMD (European or North American) and local realities, the main question that arises is: what are the various issues and challenges posed by the transition to BMD for the University of Kinshasa and, likewise, for all Congolese universities? What are the various practical constraints posed by the situation of the University of Kinshasa toward achieving such a transition? This article will try to answer these questions, beginning with the case of the University of Kinshasa.